2021
DOI: 10.1021/acsaem.0c02770
|View full text |Cite
|
Sign up to set email alerts
|

Oxychalcogenides as Thermoelectric Materials: An Overview

Abstract: Thermoelectric materials, which can convert heat into electricity and vice versa, have essential applications in power generation, thermocouples, sensors, and cooling. In the past decade, a lot of research has been devoted to developing various oxide-based thermoelectric materials, for mid- to high-temperature applications, ensuring robustness, long lifetimes, and low production costs. Among these oxide materials, one popular class is oxychalcogenides. A comprehensive discussion on the structural, electronic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 122 publications
(291 reference statements)
0
31
0
Order By: Relevance
“…Recently, BiCuOSe oxyselenides have acquired ever-increasing attention as very promising thermoelectric materials due to their high value of ZT (1.5 at 900 K) [7][8][9][10][11][12] . The outstanding TE properties could be mainly ascribed to their intrinsically low thermal conductivity of BiCuOSe and its alloys [13][14][15][16][17][18] .…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Recently, BiCuOSe oxyselenides have acquired ever-increasing attention as very promising thermoelectric materials due to their high value of ZT (1.5 at 900 K) [7][8][9][10][11][12] . The outstanding TE properties could be mainly ascribed to their intrinsically low thermal conductivity of BiCuOSe and its alloys [13][14][15][16][17][18] .…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Most TE materials currently on the market are alloys containing bismuth, antimony, and tellurium, which are rare, toxic, and/or expensive. While the highest ZT are currently obtained with chalcogenide TEs, , recent work has shown that metal oxides such as CaMnO 3 , SrTiO 3 , M 2 CoO 3 , BaTiO 3 , tungsten bronze, , Bi 2 Sr 2 Co 1.8 O y , In 2 O 3 , and La 1/3 NbO 3 may be promising alternatives to conventional TE materials while being made from cheaper, more earth-abundant, and less toxic materials. , Among the potential oxide TEs, strontium titanate (SrTiO 3 ; STO) shows promise due to its thermal stability at high temperature and tolerance to doping. ,, Bulk SrTiO 3 has a relatively poor ZT , and thus doping has been extensively explored as a possible route to improving its performance with examples including substituting Sr sites with rare-earth elements such as La , and Ti sites with other transition metals such s Nb. La doping has been shown to promote the formation of A-site vacancies, which both increases the electrical conductivity and decreases the thermal conductivity through enhanced phonon scattering . Doping with La under reducing conditions further leads to the formation of oxygen vacancies, which decreases the thermal conductivity while having minimal impact on the electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…We have used DFT-D3 method 28 to capture the weak vdWs interactions. The following plane wave basis orbitals were considered as valence electrons; Bi: 5d 10 ,6s 2 ,6p 3 ; O: 2s 2 ,2p 4 ; and S: 3s 2 ,3p 4 . A kinetic energy cutoff of 600 eV was used for plane wave basis set expansion and a spacing of 2π × 0.025 Å−1 for k-mesh in the irreducible Brillouin zone.…”
Section: Computational Details and Methodologymentioning
confidence: 99%
“…2,3 Bismuth oxychalcogenides are emerging class of materials due to their outstanding thermeoelectric and opto-electronic properties. 4 In particular, dibismuth dioxychalcogenides, Bi 2 O 2 Ch (Ch = S, Se, Te), their 2D counterparts, [5][6][7] and heterostructures 8 gained tremendous research interest due to their potential applications in thermoelectrics, 4,9,10 ferroelectrics, 11 and optoelectronics. 4,6,[12][13][14] The ternary Bi 2 O 2 Ch systems are synthesized by a solid state reaction of well-known binary thermoelectric bismuth chalcogenides Bi 2 Ch 3 (Ch = S, Se, Te) with Bi 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation